DRAWING BASED MODELLING BERBANTUAN EBEAM CAPTURE UNTUK MENSTIMULASI REPRESENTASI MIKROSKOPIS CALON GURU BIOLOGI - Hidayat, Tomi; Rahmat, Adi; Redjeki, Sri; Rahman, Taufik (Jurnal BIOEDUIN, 2019)
This study aims to determine the drawing based modeling implementation aid eBeam Capture in stimulating the Microscopic Representation of Prospective Biology Teachers in the Digital Era. This type of research is Mixed Methods Research (qualitative and quantitative mixed methods) with embedded experimental research designs. Data collection is done through interviews, observation and documentation, and tests. The results showed that in general it was seen that the microscopic representation ability of students was 77 people who scored high. The results of this study also showed that Drawing-based modeling aid eBeam Capture was able to stimulate microscopic representations of prospective teachers in Cell Biology lectures, namely by contributing 81% in Cell Biology learning. From the results of the study it can be concluded that Drawing-based modeling assisted by eBeam Capture in Biology Cell lectures can stimulate the microscopic representation of prospective biology teachers.